Variáveis hematológicas e perfil do ferro na abdominoplastia após a cirurgia bariátrica - Pedroso, Juan Carlos Montano [UNIFESP] (2011)
Background: The treatment of the abdominal wall deformity resulted from weight loss after bariatric surgery is a mixed type of abdominoplasty, which can induce post-operative anemia. In addition, bariatric surgery itself promotes a tendency to iron deficiency which could compromise erythropoiesis. To our knowledge, there is no study evaluating the degree of anemia and its recovery after post-bariatric abdominoplasty. Methods: The values of hemoglobin, reticulocytes, iron, ferritin and transferrin saturation index were measured the day prior to abdominoplasty and the first, fourth and eighth weeks after surgery. Hemoglobin was measured within 48h after surgery. Twenty adult women underwent surgery and had their data compared with 12 controls. Results: Hemoglobin levels dropped significantly from 12,98g/dL to 10,8g/dL within 48h. Hemoglobin increased significantly to 11,5g/dL by day seven, with correction of one third of the deficit, without significant increases thereafter. There was an increase in reticulocytes in the first week. Serum iron and transferrin saturation index fell in the first week and remained low. Ferritin levels showed no significant increase in the first week and subsequently fell. None of the patients received blood transfusion. Conclusion: Hemoglobin levels fell from 12,98 g/dL to 10,8 g/dL after abdominoplasty and showed an increase in the first week after surgery, with correction of one third of the deficit, but did not completely recover in the eighth week. At the end of the follow-up, 45% of the patients developed an iron deficiency and had a hemoglobin deficit higher than the patients that maintained normal iron stores.